The impact of EU-Russia sanctions on logistics operations of Finnish chemical industry - Lahtinen, Edla (My University, 2024)
The already unsteady geopolitical situation was shaken again in the February 2022, when Russia attacked Ukraine. The war is first and foremost a severe humane crisis for the Ukrainian people; the war has been the cause of one of the biggest migration crises in Finland. But the consequences of the war have not been limited on the humane side. The war was an unwanted addition to the list of geopolitical disruptions that have affected the economic world. The Covid 19 -pandemic and the so-called “trade war” between U.S. and China are examples of the disruptions that have taken place during the 2010’s and 2020’s. The war has been disapproved by the EU and for example the U.S. These countries have imposed sanctions on Russia. Sanctions are thought as a more humane way to guide the sanctioned party’s actions. The sanctions include measures on for example trade, the banking system, logistics and even singular people or organizations. The total number of the sanction packages is now, by the fall of 2024, 14. Future sanction packages have not been ruled out, since Russia has not terminated its aggression in Ukraine. It was forecasted that the sanctions would harm the Russian GDP and its economy severely but that has not happened. In fact, the Russian economy has even grown despite the sanctions. The sanctions themselves and also other impacts of the war have had their effect on the Finnish logistics infrastructure and the logistics service providers. Therefore, both the view of the infrastructure and the vies of the service providers must be covered. In the context of this thesis the parts of the logistics infrastructure and the service providers have been chosen due to their importance to the chemical industry of Finland. The consequences of the sanctions have differed between the logistics service providers. For example, VR has terminated all its operations to and from Russia. Additionally, the volumes of transit traffic from Russia through Finland have diminished significantly. Some operators have benefitted from the situation. An example of these is North Rail, which has continued to operate rail traffic between Finland and Russia. The consequences on the logistics service providers and logistics infrastructure have also influenced the chemical industry of Finland. In this thesis, a case company’s representatives were interviewed. The case company is a major operator in the Finnish chemical industry. The case company had to change its operations due to the Russian aggression. It appeared that even though the sanctions have been extensive, the industry has been able to re-configurate many of its supply chains to keep operating. Some of the solutions that were supposed to be temporary, have settled. For example, since the Saimaa Canal cannot be used, the companies that have used it have found alternative means of transport, like rail haulage.

Maailman geopoliittinen tilanne on ollut enenevissä määrin epävarma jo pitkään. Venäjän hyökättyä Ukrainaan helmikuussa 2022, epävarmuus lisääntyi entisestään. Sota Ukrainassa on ennen kaikkea humanitäärinen kriisitilanne. Sota on aiheuttanut muun muassa yhden Suomen suurimmista maahanmuuttoaalloista sotienjälkeisenä aikana. Sodalla on ollut seurauksia myös talouteen. Jo valmiiksi epävakaan geopoliittisen tilanteen taustalla vaikuttavat muun muassa koronapandemia, sekä Kiinan ja Yhdysvaltojen kauppasota. Venäjän sotatoimet Ukrainassa on tuomittu länsimaissa, varsinkin Euroopan Unionin sekä Yhdysvaltojen toimesta. Sekä Euroopan Unioni että Yhdysvallat ovat langettaneet Venäjälle ja venäläisille toimijoille erilaisia sanktioita, joiden tarkoituksena on ollut hillitä Venäjän sotatoimia Ukrainassa. Sanktiot nähdään rauhanomaisempana keinona pyrkiä vaikuttamaan sanktioidun osapuolen toimiin, kuten tässä tapauksessa sotaan. Sanktiokokonaisuuksia on syksyyn 2024 mennessä määritelty 14 kappaletta. Sota ei kuitenkaan vielä ole ohi, eivätkä sanktiot ole toimineet, kuten toivottua. Venäjän talous on jopa kasvanut, vaikka sen kaupankäynti länsimaiden kanssa on vähentynyt huomattavasti. Sanktiot ja muut sodan seuraukset ovat vaikuttaneet myös Suomen logistiikkainfrastruktuuriin sekä logistiikan palveluntarjoajiin Suomessa. Tässä tutkielmassa käsitellään näiden molempien puolien näkymiä, jotta tilanteesta voidaan saada mahdollisimman hyvä kokonaiskuva. Olennaista tässä kontekstissa on käsitellä niitä logistiikkainfrastruktuurin osia sekä palveluntarjoajia, jotka liittyvät olennaisimmin suomalaiseen kemianteollisuuteen. Sanktioiden seuraukset ovat vaihdelleet logistiikan toimijoiden välillä. Tosin, esimerkiksi VR ei lopettanut toimintaansa Venäjällä sanktioiden vuoksi, vaan eettisistä syistä. Lisäksi, transitoliikenteen määrät Venäjältä ovat vähentyneet huomattavasti, mikä on vapauttanut kapasiteettia satamista. Toiset toimijat ovat hyötyneet tilanteesta: North Rail on jatkanut operointia Suomen ja Venäjän välisessä liikenteessä. Tätä tutkielmaa varten haastateltiin merkittävän Suomessa toimivan kemianteollisuuden yrityksen työntekijöitä. Kyseisen yrityksen oli muutettava logistisia toimintatapojaan ja operaatioitaan sotatilanteen ja sen seurausten vuoksi huomattavasti. Sanktioiden kattavuuden vuoksi, yritysten on täytynyt järjestellä uudelleen toimitusketjujaan liiketoimintansa jatkuvuuden turvaamiseksi. Jotkut alun perin väliaikaisiksi suunnitellut ratkaisut ovat muuttuneet jo vakiintuneemmiksi tavoiksi toimia. Esimerkiksi Saimaan kanavan käytön estyttyä yritykset ovat siirtyneet esimerkiksi rautatiekuljetuksiin.
Keywords: chemical industry, geopolitics, logistics, supply chain configuration